Flexural strengthening of RC slabs with prestressed CFRP strips using different anchorage systems - Sena-Cruz, José (2015)
Externally Bonded Reinforcement (EBR) technique has been widely used for flexural strengthening of concrete structures by using carbon fiber-reinforced polymers (CFRP). EBR technique offers several structural advantages when the CFRP material is prestressed. This paper presents an experimental and numerical study on reinforced (RC) slabs strengthened in flexure with prestressed CFRP strips as a structural strengthening system. The strips are applied as an externally bonded reinforcement (EBR) and anchored with either a mechanical or a gradient anchorage. The former foresees metallic anchorage plates fixed to the concrete substrate, while the latter is based on an accelerated epoxy resin curing followed by a segment-wise prestress force decrease at the strip ends. Both anchorage systems, in combination with different CFRP strip geometries, were subjected to static loading tests. It could be demonstrated that the composite strip’s performance is better exploited when prestressing is used, with slightly higher overall load carrying capacities for mechanical anchorages than for the gradient anchorage. The performed investigations by means of a cross-section analysis supported the experimental observation that in case a mechanical anchorage is used, progressive strip debonding changes the fully bonded configuration to an unbonded end-anchored system. The inclusion of defined debonding criteria for both the anchorage zones and free length between the anchorage regions allowed to precisely capture the ultimate loading forces.